PENGARUH TERAPI AKUPRESUR TERHADAP FREKUENSI ENURESIS PADA ANAK USIA PRA SEKOLAH DI TK ANNA HUSADA BANGKALAN - Novi Anggraeni (NHM PRESS, 2019)
Enuresis called bedwetting is a problem in pre school children which have overcome, because actually at this period the child shall could to controlling their bladder. Enuresis can also effected the quality of social and psychological of the children moreover the quality of the child growing to adult. Required serious handling until growing problem of this development, one of them is a complementary therapy acupressure. This study purpose to determinate the effect of acupressure therapy to the enuresis frequency of a pre school children. Characteristic of this research is quantitative research with used pre experimental research design with one group pre test – post test design without the control group. The population of this research were 20 children, and the sample were 19 respondents with Purposive Sampling technique that given acupressure therapy 3 times in 1 week with 15 minutes duration per intervention. The analysis method is Paired Sample T- Test. The result of Paired Sample T – Test shown that the enuresis frequency average before given acupressure therapy is 4.36 per week and the enuresis frequency average after given acupressure therapy is 3,10 per week, with the 0,000 significancy ( p < 0,05 ). The value shown that acupressure therapy is effected to the enuresis frequency of a pre school children at the ANNA HUSADA kindergarten, Bangkalan. Parents which have the pre school child with the enuresis problem, should to be resolve enuresis problem at the early time, also can do acupressure therapy exactly and goodly.